2005
DOI: 10.1002/crat.200410389
|View full text |Cite
|
Sign up to set email alerts
|

FT‐IR spectroscopic and thermal studies on pure and impurity added calcium tartrate tetrahydrate crystals

Abstract: Pure and impurity (strontium) added calcium tartrate tetrahydrate single crystals were grown by the gel method. The FT-IR spectra of these crystals were recorded in the wavenumber range 400 -4000cm. The thermograms of the grown crystals were recorded in the temperature range 50 -900 o C. FT-IR spectra reveals the presence of water molecules, O-H bond, C-O and carbonyl C=O bonds. The thermograms show that these crystals are thermally unstable and decompose into its oxide through many stages. DTA curve of the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Joshi and Joshi [11] as well as Sahaya Shajan and Mahadevan [12] have reported FT-IR spectrum of pure calcium tatrate crystals. Recently, FT-IR spectroscopic study has been reported in strontium added calcium tatrate crystals [4]. The absorptions occurring between 3100 cm -1 to 3300 cm -1 are due to the asymmetric and symmetric stretching of O-H bond, which is generally indicating the presence of water of crystallization.…”
Section: Different Environment Of Mnmentioning
confidence: 99%
See 1 more Smart Citation
“…Joshi and Joshi [11] as well as Sahaya Shajan and Mahadevan [12] have reported FT-IR spectrum of pure calcium tatrate crystals. Recently, FT-IR spectroscopic study has been reported in strontium added calcium tatrate crystals [4]. The absorptions occurring between 3100 cm -1 to 3300 cm -1 are due to the asymmetric and symmetric stretching of O-H bond, which is generally indicating the presence of water of crystallization.…”
Section: Different Environment Of Mnmentioning
confidence: 99%
“…Structural characterization of doped calcium tartrate tetrahydrate (CTT) crystals was extensively carried out by Torres et al [3]. The exploration of doped CTT crystals continued and recently Sahaya Shajan and Mahadevan [4] reported FT-IR and thermal studies of impurity added CTT crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The metal tartrate compounds find various applications in different fields, for example, application of tartrate ions to treat prostate cancer [1], iron tartrate complex ions play important role as contrast blocks of renal tissues prior to their dehydration [2], iron tartrate is one of the prominent species in apple juice [3], calciphylatic responses of various ferrous tartrate compounds to prevent anemia in animals [4], the potential for iron(III) tartrate to act as a photo activator in light-induced oxidative degradation of white wine [5], ferroelectric, dielectric, optical and thermal properties of calcium tartrate [6], piezoelectric application of cadmium tartrate [7] and the addition of lead tartrate in gasoline to prevent knocking in motors [8]. The gel growth technique is found to be suitable to grow tartrate compound crystals and many authors have reported the growth of metal tartrate crystals [9][10][11][12], mixed metal tartrate crystals [13,14] and ternary metal tartrate crystals [15,16] in gel medium.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have studied the growth of calcium tartrate crystals in a silica hydro-gel media [5][6][7]. Calcium tartrate crystals are well known for its ferroelectric properties in pure [8] as well as doped forms [9] and their structural characterization [10] and FT-IR and thermal properties [11] have been reported. There are several applications of calcium tartrate crystals.…”
Section: Introductionmentioning
confidence: 99%